2016
DOI: 10.1097/md.0000000000003970
|View full text |Cite|
|
Sign up to set email alerts
|

IgG4-related disease involving vital organs diagnosed with lip biopsy

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a recently recognized new disease entity characterized by elevated serum IgG4 and infiltration of IgG4+ plasma cells in affected tissues. Histological examination is essential for definitive diagnosis, as other pathological conditions can also present with serum IgG4 elevation. However, IgG4-RD frequently involves vital or internal organs that are difficult to perform biopsies. We herein report a unique case of IgG4-RD involving vital organs that could be successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…( 76 ) examined the ectopic formation of GC and the expression of IL-21, Th2-, Th17-, and Tfh-related cytokines in 12 patients with Mikulicz’s syndrome and found that IL-4-expressing Tfh cells were primarily located outside of the ectopic GCs, whereas IL-21-expressing Tfh cells were located inside. Similarly, the upregulated expression of IL-21 mRNA was associated with the formation of ectopic GCs ( 76 , 77 ). Thus, GC formation, B cell selection, and IgG 4 antibody class-switch via different Tfh cell-produced cytokines are basic pathological events in the progression of IgG 4 -RD.…”
Section: Adaptive Immunitymentioning
confidence: 95%
“…( 76 ) examined the ectopic formation of GC and the expression of IL-21, Th2-, Th17-, and Tfh-related cytokines in 12 patients with Mikulicz’s syndrome and found that IL-4-expressing Tfh cells were primarily located outside of the ectopic GCs, whereas IL-21-expressing Tfh cells were located inside. Similarly, the upregulated expression of IL-21 mRNA was associated with the formation of ectopic GCs ( 76 , 77 ). Thus, GC formation, B cell selection, and IgG 4 antibody class-switch via different Tfh cell-produced cytokines are basic pathological events in the progression of IgG 4 -RD.…”
Section: Adaptive Immunitymentioning
confidence: 95%
“…Clinicians could forgo further biopsy if such patients respond well to glucocorticoids within weeks, such as reductions in the size of tumors, improvements of symptoms and a significant decrease in serum IgG4 [20]. Alternative non-vital organ or lip biopsy may be an acceptable option [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrozis ve obliteratif flebit bazen submandibuler bezlerdeki doku örneklerinde bulunur. Minör tükürük bezi biyopsiside IgG4 hastalığını teşhis etmek için kullanılabilir (19). Primer sjögren sendromu ile ayrımında; serolojik testlerin negatifliği (antinükleer antikor, anti-Ro / SSA ve anti-La / SSB otoantikorları), daha yüksek bir alerjik rinit ve bronşiyal astım sıklığı, tükürük ve gözyaşı bezlerinin büyük olmasına rağmen ağız ve göz kuruluğunun hafif olması ile klinik olarak ayrım sağlanabilir.…”
Section: Tükürük Ve Gözyaşı Bezi Tutulumuunclassified